2020
DOI: 10.2139/ssrn.3723117
|View full text |Cite
|
Sign up to set email alerts
|

Wind Generation and the Dynamics of Electricity Prices in Australia

Abstract: Australia's National Electricity Market (NEM) is experiencing one of the world's fastest and marked transitions toward variable renewable energy generation. This transformation poses challenges to system security and reliability and has triggered increased variability and uncertainty in electricity prices. By employing an exponential generalized autoregressive conditional heteroskedasticity (eGARCH) model, we gauge the effects of wind power generation on the dynamics of electricity prices in the NEM. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In general, increasing penetration of VRE is associated with a lower average wholesale price of electricity. This behaviour has been found in both domestic (4)(5)(6)(8)(9)(10)(11)(12)(12)(13)(14)(15)(16)(17)(18)(19)26) and some international (22)(23)(24)(25)27,28) electricity markets. A summary of the domestic studies can be found in Supplementary Materials (Table S1).…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…In general, increasing penetration of VRE is associated with a lower average wholesale price of electricity. This behaviour has been found in both domestic (4)(5)(6)(8)(9)(10)(11)(12)(12)(13)(14)(15)(16)(17)(18)(19)26) and some international (22)(23)(24)(25)27,28) electricity markets. A summary of the domestic studies can be found in Supplementary Materials (Table S1).…”
Section: Introductionmentioning
confidence: 72%
“…There are also instances where solar energy penetration have abated temporal price volatility (33,35). The evidence from literature suggests that the relationship between temporal price volatility and VRE penetration can vary widely as a result of a confluence of several factors, including patterns of demand (34), weather (22), and the availability of flexible generation (33). In 5 of the 6 ISOs we studied, the system temporal price volatility decreased as the penetration of VRE increased across all quantiles.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations